Reconstructing environments of collection sites from archaeological bivalve shells: Case study from oysters (Lyon, France). (October 2018) - Mouchi, Vincent; Briard, Justine; Gaillot, Stéphane; Argant, Thierry; Forest, Vianney; Emmanuel, Laurent
Abstract: The flat oyster, Ostrea edulis, was consumed as a luxury dish by the Romans in antiquity. Numerous shells are found in archaeological sites in the Lyon region, Central France. This area is located over 250 km away from the nearest coastline (the Mediterranean Sea) and little is known about the origin of these oysters prior to transport for consumption. The chemistry of biogenic carbonates reflects that of the fluid they precipitate from at the time of formation. Stable isotopes and Mg/Ca ratios in oyster shells have previously been used as palaeoenvironmental proxies. As Mg/Ca ratio amplitude in bivalve shells has been reported to differ according to local hydrologic settings, we suggest that geochemical differences observed in each shell can be used to identify the type of environment (e.g. estuary, lagoon or marine) from which the specimens originated. In this study, we analyzed the elemental composition of six archaeological O. edulis shells of unknown provenance, collected in the Lyon region dated from the 3rd century AD to the 5th century AD. In addition, stable carbon and oxygen analyses from three of these specimens were performed to reconstruct intra-annual fluctuations of seawater chemistry. Overall results show a strong heterogeneity in values. One shell exhibits large fluctuations in δ 13 C (from − 2 to 1‰) and δ 18 O (from − 2 to 3‰), interpreted as evidence for an estuarine origin. The Mg/Ca amplitude (from 5 to 35 mmol·mol − 1 ) also indicates proximity to a river outlet, as such values were previously reported from modern estuarine oyster shells. Two other specimens present a restricted amplitude in Mg/Ca values (from ~ 0 to 5 mmol·mol − 1 ), similar to values measured in modern open marine locations. Four other specimens exhibited intermediate Mg/Ca ratios and more restricted stable isotope composition ranges which indicate that these specimens lived in waters with limited freshwater input. The geochemical data from these shells support the hypothesis that fishermen of Antiquity collected oysters from a variety of environments/locations. A clear identification of the living localities of these specimens is still to be defined, as the present data cannot discriminate whether these shells originated from the Mediterranean Sea or the Atlantic Ocean coastline. Highlights: The origin of bivalve shells found in Gallo-Roman antiquity sites in Lyon, France, is unknown. Six oyster shells from antique sites are analyzed for stable isotopes and Mg/Ca. Geochemistry can provide information on the environment of oysters living localities. Mg/Ca range values in oyster shells can indicate the type of environment. Shells exhibit different compositions which are interpreted as different environments.